Challenges and Strategies of Mental Health Professionals Working with the Elderly in Malaysia - Hui Sian, Chin; Asmah, Ismail (UNIMAS Publisher, 2023)
Malaysia is expected to be an ageing nation by 2030, in which the elderly will make up at least 15% of the total population. As a result, there is a growing demand for well-trained mental health professionals (MHPs) to address the psychosocial and mental health issues faced by the elderly. To provide quality mental health care for the elderly, it is crucial for MHPs to equip themselves with the necessary knowledge, skills, and competencies to understand their unique needs and challenges. The aim of this qualitative phenomenological study was to explore the challenges and coping strategies of MHPs working with the elderly. Through in-depth interviews with five MHPs, the study identified several challenges, including stereotypes held by the elderly towards mental health services, communication barriers, and the impact of COVID-19 on the mental health of the elderly. The MHPs addressed these challenges using coping strategies such as increasing mental health awareness and support for the elderly, using appropriate communication methods, and facilitating access to mental health care. Future studies with a more significant number of MHPs from diverse demographic backgrounds and varying levels of working experience are recommended to gain a deeper understanding of the challenges involved in psychotherapy with the ageing population and identify optimal ways to overcome them.